Pembuatan Konten Media Pembelajaran Berbasis Multimedia bagi Guru SMP PGRI 1 Buduran Sidoarjo - Sunyoto Hadi Prayitno; Eko Sugandi; Nur Fathonah; Rani Kurnia Putri; Sri Rahmawati Fitriatien (Fakultas Ekonomi, Universitas PGRI Adi Buana Surabaya, 2022)
This community service program aims to add and improve teacher skills in creating multimedia-based learning media content and can develop interactively. Through this service activity, teachers at SMP PGRI 1 Buduran Sidoarjo can use Quizizz as an alternative interactive media used in limited online and offline learning. This service activity is carried out offline by a team of lecturers for the Mathematics Education study program at Universitas PGRI Adi Buana Surabaya. The target of the activity is all teachers who are divided into various subject teachers. This activity received full support from the principal and all teachers so that it could run well and smoothly starting from the observation of the activity to the end of the activity.